2002
DOI: 10.1097/00042737-200201000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Helicobacter pylori eradication in uninvestigated chronic dyspeptic staff members of a large factory: a prospective, long-term, follow-up, workplace outcome study

Abstract: These data suggest that an H. pylori test-and-treat strategy in occupational medicine is effective for improving uninvestigated dyspepsia and quality of life and it may reduce dyspepsia related health care costs at a level of occupational medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Madisch et al 38 investigated the outcome of H. pylori eradication in staff members with uninvestigated chronic dyspepsia in a large factory in a prospective, open-label, controlled, workplace outcome study after 1 year of follow-up of dyspepsia, and quality of life. H. pylori status was assessed using the 13 C-urea breath test in 267 individuals with dyspepsia.…”
Section: Prospective Studies (Not Rcts)mentioning
confidence: 99%
“…Madisch et al 38 investigated the outcome of H. pylori eradication in staff members with uninvestigated chronic dyspepsia in a large factory in a prospective, open-label, controlled, workplace outcome study after 1 year of follow-up of dyspepsia, and quality of life. H. pylori status was assessed using the 13 C-urea breath test in 267 individuals with dyspepsia.…”
Section: Prospective Studies (Not Rcts)mentioning
confidence: 99%
“…Madisch et al studied the outcome of Hp eradication in 267 factory workers from Germany who reported uninvestigated chronic dyspepsia ( Madisch et al, 2002 ). They assessed Hp infection status at baseline using the 13C-UBT, and positive workers (N = 111, 41.6%) were offered eradication therapy.…”
Section: Screening Working Populations For Helicobacter Pylorimentioning
confidence: 99%